Cryptococcus neoformans in the nasal cavity of a cat in Costa Rica. A case report (Ciencias Veterinarias, 2018)
Feline cryptococosis is caused by the encapsulated yeasts of the complex Cryptococcus neoformans and Cryptococcus gattii. This is the most frequent mycosis in cats that could be either asymptomatic or with respiratory and neurologic signs. No cases have been reported in Costa Rica. A crossbreed, shorthair, male cat of 4 years old with refractory 6 months sneezing, unilateral nasal discharge, was examined. A biopsy of nasal mucosal tissue and a nasal lavage were performed in order to carry out cytological and mycological analysis. A pyogranulomatous process with several encapsulated yeasts were observed in the cytology. Encapsulated yeasts were also observed in the direct microscopic examination using KOH, Indian Ink and in the smear stained with Giemsa. Cryptococcus sp. was isolated from tissue cultures and was confirmed as C. neoformans by API 20C AUX (Biomérieux®). The cat was treated during 9 months with satisfactory clinical results. Cryptococcosis must be considered in the differential diagnosis of feline patients with chronic and colorless unilateral nasal discharge. Confirmation must be performed by laboratory tests in order to set up the appropriate treatment.